IDENTIFICATION AND IMPLEMENTATION OF DESIGN PATTERNS IN MOBILE BANKING (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
The aim of this paper is to develop a mobile banking system using design patters that provides customers with the facility to check their accounts and to do online transactions using mobile phones. There are various number of software design patterns that have been identified and used by software developers in various domains such as navigation systems, e-commerce, data mining, construction of operating systems, e-business, games and website designing and development purpose. In order to achieve our aim we are going to follow three steps. First step is the identification process, in this process we are going to study the various design patterns and the existing architecture of several mobile banking systems and will identify the design patterns based on the cross cutting concerns that occur in flow of the banking process. The second step is to implement the identified design patterns using the patterns skeleton code. We need to improve the reusability using object oriented programming. Finally we are going to implement the identified patterns and evaluate the patterns using already available methods such as SAAM, ATAM, ALAM (Architecture-Level Maintainability Analysis).